2011
DOI: 10.1007/s11105-011-0294-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Iranian Accessions, Improved Lines of Chickpea (Cicer arietinum L.) and Their Wild Relatives by Using Simple Sequence Repeats

Abstract: Biodiversity information in available germplasm is very useful for the success of any breeding program. To establish genetic diversity among 44 genotypes of chickpea comprising cultigen, landraces, internationally developed improved lines and wild relatives, genetic distances were evaluated using 19 simple sequence repeat markers with 100 marker loci. Estimation of the number of alleles per locus (n a ), the effective allele number (n e ), and Wright fixation index F were 6.25, 3.67, and 0.44, respectively.Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 55 publications
5
27
2
2
Order By: Relevance
“…Detailed information on the levels of genetic diversity of genotypes is available elsewhere (Saeed et al, 2011). Analysis of population structure distinguished 6 subspecific populations (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed information on the levels of genetic diversity of genotypes is available elsewhere (Saeed et al, 2011). Analysis of population structure distinguished 6 subspecific populations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The present study used 16 pairs of SSR primers and subdivided the association population into six subpopulations using the modelbased cluster method. Data from our genetic diversity (Saeed et al, 2011) and population structure analysis revealed that this association population showed a diverse genetic variation and, therefore, could be used for the association analysis. Among factors influencing marker-traits association, the admixture of populations is very important (Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…but was not consistent with reports of Byrne, and Matsumoto and collab. who reported a low level of genetic diversity within rose germplasm [SAEED et al, 2011, GHAFFARI et al, 2014, BYRNE, 1999, MATSUMOTO et al, 1998] .…”
Section: Comparison Among the Studied Markersmentioning
confidence: 99%
“…It is cultivated in about 33 countries and regions including Central-West Asia, South Europe, Ethiopia, North Africa, and Australia (FAO, 2013;ICRISAT, 2013). It has high nutritive value and serves as an important cheap source of protein in developing countries in addition to improving land fertility (Saeed et al, 2011). The chickpea seed is a good source of carbohydrates and proteins, which collectively constitute 80% of the total dry seed weight (Talebi et al, 2008;Aggarwal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%